The Class III PI3K/Beclin-1 Autophagic Pathway Participates in the mmLDL-Induced Upregulation of ETA Receptor in Mouse Mesenteric Arteries. (1st April 2020) - Xie, Xi; Chen, Chen; Xu, Cang-Bao; Lin, Jie; Cao, Lei; Chen, Gen; Li, Jie
Abstract : Minimally modified low-density lipoprotein (mmLDL) is a risk factor for cardiovascular diseases. The current study explored the effect of mmLDL on the endothelin type A (ETA) receptor in mouse mesenteric arteries in vivo, as well as the role of autophagy in this process. mmLDL was injected via the caudal vein, and the Class III PI3K autophagic pathway inhibitor 3-methyladenine (3-MA) was injected intraperitoneally. The animals were divided into physiological saline (NS), mmLDL, and mmLDL + 3-MA groups. The dose-effect curve of endothelin-1- (ET-1-) induced mesenteric artery contraction was measured using myography, while ETA receptor mRNA expression was detected using real-time polymerase chain reactions, and the protein levels of the ETA receptor, class III PI3K, Beclin-1, LC3 II/I, p62, NF- κ B, and p-NF- κ B were observed using Western blot analysis. mmLDL significantly strengthened ET-1-induced contraction (the E max value increased from 184.87 ± 7.46% in the NS group to 319.91 ± 20.31% in the mmLDL group (P < 0.001 ), and the pEC50 value increased from 8.05 ± 0.05 to 9.11 ± 0.09 (P < 0.01 ). In addition to upregulating the protein levels of Class III PI3K, Beclin-1, and LC3 II/I and downregulating that of p62, mmLDL significantly increased the mRNA expression and protein level of the ETA receptor and increased the protein level of p-NF- κ B. However, these effects were significantly inhibited by 3-MA. mmLDL activates autophagy via the Class III PI3K/Beclin-1 pathway and upregulates the ETA receptor via the downstream NF- κ B pathway. Understanding the effect of mmLDL on the ETA receptor and the underlying mechanisms may provide a new idea for the prevention and treatment of cardiovascular diseases.